Skeletal Muscle Mass Has Stronger Association With the Risk of Hyperuricemia Than Body Fat Mass in Obese Children and Adolescents - Xie, Luyao; Mo, Phoenix K. H.; Tang, Qingya; Zhao, Xuan; Zhao, Xuelin; Cai, Wei; Feng, Yi; Niu, Yang (Frontiers in Nutrition, 2022)
Background: Hyperuricemia has been increasing among children with obesity in recent years, but few studies explored the relationship between obesity-anthropometric indexes and hyperuricemia in them. This study aimed to examine the associations between hyperuricemia and different body components in children and adolescents with obesity, and further explore gender differences in these associations. Methods: In this cross-sectional study, a total of 271 obese children and adolescents (153 boys and 118 girls) aged 6-17 years were recruited from Shanghai Xinhua Hospital. Data about basic information, anthropometric assessments, body composition and laboratory tests of participants were collected. Results: In this study, 73 boys (47.71%) and 57 girls (48.31%) were diagnosed to be hyperuricemia. The impacts of percentage of skeletal muscle (OR = 1.221, P < 0.001) and skeletal muscle mass (OR = 1.179, P < 0.001) on the risk of hyperuricemia was the largest, followed by hip circumference (OR = 1.109, P < 0.001), waist circumference (OR = 1.073, P < 0.001) and body fat mass (OR = 1.056, P < 0.05) in whole sample, adjusted for age, gender and body mass index. After stratified by gender, percentage of skeletal muscle (boys: OR = 1.309, P < 0.001) and skeletal muscle mass (boys: OR = 1.200, P < 0.001; girls: OR = 1.147, P < 0.05) were still the most predictors of hyperuricemia, followed by hip circumference (boys: OR = 1.147, P < 0.001; girls: OR = 1.080, P < 0.05). Waist circumference showed a significant association with hyperuricemia only in boys (OR = 1.083, P < 0.05), and body fat mass showed no association with hyperuricemia in both gender groups after adjusting for age and body mass index. Conclusions: Our findings suggested that skeletal muscle mass was a stronger predictor in hyperuricemia than body fat mass in children and adolescents with obesity, especially in boys.